INFLUENCE OF SULFUR ON THE STRUCTURE AND CHARACTERISTICS OF ALUMINUM ALLOYS - B. M. Nemenenok; A. M. Galushko; G. V. Dovnar; S. P. Zadrutskij; I. I. Bajeshko (Литьë и металлургия, 2005)
The fining compounds on the basis of sulfur are offered. Their influence on the structure and characteristics of aluminium alloys is shown.